Fluent Speakers of a Second Language Process Graspable Nouns Expressed in L2 Like in Their Native Language - Buccino, Giovanni; Marino, Barbara F.; Bulgarelli, Chiara; Mezzadri, Marco (Frontiers in Psychology, 2017)
According to embodied cognition, language processing relies on the same neural structures involved when individuals experience the content of language material. If so, processing nouns expressing a motor content presented in a second language should modulate the motor system as if presented in the mother tongue. We tested this hypothesis using a go-no go paradigm. Stimuli included English nouns and pictures depicting either graspable or non graspable objects. Pseudo-words and scrambled images served as controls. Italian participants, fluent speakers of English as a second language, had to respond when the stimulus was sensitive and refrain from responding when it was not. As foreseen by embodiment, motor responses were selectively modulated by graspable items (images or nouns) as in a previous experiment where nouns in the same category were presented in the native language.